2023
DOI: 10.1021/acsami.3c10994
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Antibiotic and Protein-Stabilized Nanosilver into Sandwich-Structured Electrospun Nanofibrous Scaffolds for MRSA-Infected Wound Treatment

Ling Cai,
Li Zhang,
Jing Yang
et al.

Abstract: With the increasing prevalence of microbial infections, which results in prolonged inflammation and delayed wound healing, the development of effective and safe antimicrobial wound dressings of multiple properties remains challenging for public health. Despite their various formats, the available developed dressings with limited functions may not fulfill the diverse demands involved in the complex wound healing process. In this study, multifunctional sandwich-structured electrospinning nanofiber membranes (ENM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…As the largest multifunctional organ of the human body, skin serves as a natural barrier to protect against external stimuli and regulate body metabolism. The treatment of skin damage is a common problem in daily life, and wound dressings are the primary clinical therapies to promote wound healing and maintain physical health. While current dressings still have issues with inaccurate inflammation control and insufficient comprehensive functionality, which causes delayed healing. , It is important to analyze the healing mechanism and develop versatile dressings to enhance wound healing. Recent studies have shown that the endogenous electric field (EF), generated by the directional ion flow following skin injury, has a substantial impact on the stimulation of cell proliferation and migration .…”
Section: Introductionmentioning
confidence: 99%
“…As the largest multifunctional organ of the human body, skin serves as a natural barrier to protect against external stimuli and regulate body metabolism. The treatment of skin damage is a common problem in daily life, and wound dressings are the primary clinical therapies to promote wound healing and maintain physical health. While current dressings still have issues with inaccurate inflammation control and insufficient comprehensive functionality, which causes delayed healing. , It is important to analyze the healing mechanism and develop versatile dressings to enhance wound healing. Recent studies have shown that the endogenous electric field (EF), generated by the directional ion flow following skin injury, has a substantial impact on the stimulation of cell proliferation and migration .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] The mechanism of antimicrobial nanomaterials enables them to eliminate resistant pathogenic microorganisms in environmental and healthcare applications, while down regulating their drug resistance genes and avoiding targeted resistance of bacteria, which is of great significance for controlling nosocomial infections and protecting public health. [23] Metal-organic framework (MOF) materials have been widely used for antimicrobial applications. [24][25][26][27] MOFs materials can also be used as capacitors, sensors, adsorption materials, catalytic materials, drug slow-release carriers, etc.…”
Section: Introductionmentioning
confidence: 99%